Clinically relevant outcome measures of novel pharmacotherapy for nonallergic rhinitis. Issue 3 (June 2015) - Brown, Kari R.; Bernstein, Jonathan A.
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this review is to briefly provide the current understanding of the pathogenesis of nonallergic rhinitis (NAR), currently available pharmacotherapies as well as some recent advancement in pharmacotherapy for this condition. With this background on NAR, we then describe and contrast outcome measures used in previous NAR and allergic rhinitis clinical trials. Finally, we conclude with a brief discussion on which of these outcomes might be most suitable for future NAR clinical trials. Recent findings NAR is a heterogeneous condition in which multiple mechanisms have been postulated to be involved. Patients with NAR commonly experience chronic nasal congestion and anterior and/or posterior drainage, which significantly affects their quality of life. Current standard of care is primarily symptom based, as specific therapies that target the underlying mechanisms of this condition are lacking. As there are no current treatment algorithms for NAR, clinical response and outcomes can vary widely between patients. Intranasal corticosteroids and intranasal antihistamines have been found to be effective in well designed clinical trials in the treatment of NAR and are therefore considered first-line therapies. Recently, studies investigating a combination of intranasal antihistamine/corticosteroid and an intranasal decongestant and with an intranasal corticosteroid have shown promise for allergic rhinitis and may also be more effective than monotherapy for NAR. Multiple outcome measures have been used in previous NAR trials, the most common being variations of nasal symptoms scores. Given the differences in prominent symptoms typically experienced by allergic rhinitis and NAR, accurate clinical outcomes used to evaluate new treatments for these two patient groups will likely differ. Further studies specifically designed to investigate the efficacy of various therapeutic agents in NAR are required to improve the management and outcomes of this chronic condition. Summary Further research is required to expand our understanding of the pathobiology of NAR that should lead to novel therapeutic approaches for managing this condition. It will be necessary to have well established validated NAR outcomes that can be used to study these novel therapies.